Explaining state investment in drinking water infrastructure for disadvantaged communities, 1997-2016 - Xi Chen; Jonathan M. Fisk; John C. Morris; Ryan P. Scott (Utilities Policy, 2026)

Species nativeness as a cultural paradigm in conservation - Lily M. van Eeden; Jeff Vance Martin; Jonathan Fisk; Lisa Lehnen; Erle C. Ellis; Michael C. Gavin; Adam C. Landon; Lincoln R. Larson; Kirsten M. Leong; Wayne Linklater; Christopher K. Williams; Richard E.W. Berl (Biological Conservation, 2025)

The generations of cultural ecosystem services research - Rachelle K. Gould; Terre Satterfield; Kirsten Leong; Jonathan Fisk (Conservation Biology, 2025)
Understanding the cultural dimensions of human–nature relationships and integrating them into decision‐making is a central goal of conservation social science. One prominent avenue for this work is the characterization and analysis of cultural ecosystem services (CES) (i.e., nonmaterial aspects of the benefits derived from human–nature relationships). The Millennium Ecosystem Assessment introduced the term CES in 2005, and the ensuing decades have seen a blossoming of work on this topic—including extensive critique and the development of multiple closely related concepts. Because the need to recognize CESs (by whatever name) is not going away, we reflected on where CES research has been, where it is now, and where it might go. We refer to the current field as second‐generation CES: a suite of approaches and innovations (biocultural indicators, relational values, and nonmaterial nature's contributions to people) that enhance, reject, or modify some of the premises of first‐generation CES. These new approaches can be understood as a pluralistic menu of options to capture the essence of what CES aimed to, or failed to fully, represent. Nonmaterial factors (i.e., CES and conceptual offspring of CES) can affect conservation decision‐making via 4 main channels: evaluation or assessment, elucidation of trade‐offs, epistemic and social recognition, and, in some cases, the reclassification of what nature itself is.

Un‘covering’ blanket bonds: Assessing the adoption of blanket bonds across the states - Nurun Naher; Adam P. Mayer; Jonathan M. Fisk; John C. Morris (The Extractive Industries and Society, 2023)

Erratum to: Can Local Voluntary Environmental Programs ‘‘Work’’? An Examination of Fort Collins’ (Colorado) Climate Wise Program - Samantha Mosier; Jonathan Fisk (Environmental Management, 2013)

Can Local Voluntary Environmental Programs “Work”? An Examination of Fort Collins’ (Colorado) Climate Wise Program - Mosier Samantha; Fisk Jonathan (Environmental Management, 2013)